Cloning and determination of the transcription termination site of ribosomal RNA gene of the mouse. - Kominami, R (1982)
A Eco RI 6.6 kb DNA fragment containing the 3'-end of 28S ribosomal RNA gene of the mouse was detected by Southern blot hybridization, and cloned in a lambda-phage vector. The site of transcription termination and the processed 3'-end of 28S RNA were determined on the cloned fragment and the surrounding nucleotide sequence determined. The 3'-terminal nucleotides of mouse 28S RNA are similar to those of yeast, Drosophila and Xenopus although the homology was lost drastically beyond the 3'-end of 28S RNA. 45S precursor RNA terminated at 30 nucleotides downstream from the 3'-end of 28S RNA gene. A structure of a dyad symmetry with a loop was found immediately prior to the termination site of 45S RNA. The rDNA termination site thus shares some common features with termination sites recognized by other RNA polymerases.